Thozetella species (anamorphic fungi – Hyphomycetes) from Semi-Arid of Bahia State, Brazil - Barbosa, Flávia Rodrigues; Gusmão, Luís Fernando P.; Barbosa, Fabio Fernandes (SITIENTIBUS série Ciências Biológicas, 2007)
This paper deals with the occurrence of three species of the genus Thozetella Kuntze found on decaying leaves in the semi-arid region of Bahia State, Brazil: T. cristata Piroz. & Hodges, T. cubensis R.F.Castañeda & G.R.W. Arnold, and T. havanensis R.F. Castañeda. Description and illustrations are provided for T. havanensis, a new register for Bahia State. A taxonomic key with all species of Thozetella collected in Brazil is added.